Pengelolaan Program Karakter Religius Di MTS Negeri 2 Bengkulu Utara - Nopitri , Diana; Sumarsih; Connie (Manajer Pendididikan, 2024)
The aim of the research is to describe the management of the religious character program at MTs Negeri 2 North Bengkulu. This study used descriptive qualitative method. Data collection techniques use observation, documentation and interviews. Data analysis techniques consist of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that planning was carried out to form a special work team known as the religious character program activity work team, implementation was carried out in a scheduled and programmed manner, evaluation results were carried out every six months by all teachers to measure the success of the program created, and inhibiting factors in the process. management, namely the lack of facilities and infrastructure, budgets and the lack of awareness among each student in cultivating religious character. The strategy used in managing the religious character program can be overcome by making a joint commitment with the school, students and parents and providing understanding. knowledge, good role models and good habits.